no tiene Multiculturalidad e inclusión política en México - Lozano alvarado, Justino (Instituto de Investigaciones Socioeconómicas, 2021)
At a conceptual level, the category of cultural citizenship, referring to collective identities as the right to difference, identity and self-government of indigenous peoples; it is gaining more and more strength and earthiness, thanks to the indigenous movement and to some extent, from another angle, to the debate between liberals and multiculturalists, who have opened a democratic vision of societies, more plural and of justice.The international recognition of cultural rights, and the legislative reforms in each nation, show the construction of this civic dimension, based on social movements -among them indigenous-, which are claiming political rights, such as cultural rights and collective rights. With which it could be said that, to a large extent, sociocultural democracy is above all a project that has been becoming a reality, making progress in the debate of the concept of citizenship concomitant to the problems derived from cultural identities and differences, in multicultural contexts. This trend raises a horizon of possibilities for the concept of cultural citizenship that enhances the more global democratic construction of society.